Tumor Anti-Initiation and Anti-Progression Properties of Sulphated-Extract of Colocasia esculenta - Amira M. Gamal-Eldeen; Hassan Amer ‎; Cinderella A. ‎ Fahmy; Haytham ‎ Dahlawi; Basem H ‎ Elesawy; Nahla L. ‎ Faizo; Bassem M. ‎ Raafat (Polish Journal of Food and Nutrition Sciences)
Colocasia esculenta (Taro) is an edible tuberous plant; however, corms are its most worldwide consumed part while the corm powder is widely used in food industries. In this work, a sulphated polysaccharide extract of C. esculenta corm (SCE) was prepared and its cancer chemopreventive properties were explored. The amending of carcinogen metabolism and radical scavenging affinity revealed that SCE is a strong tumor anti-initiation agent via suppressing cytochrome P450-1A and enhancing glutathione and the carcinogen detoxification enzyme; glutathione S-transferase. SCE exhibited a strong scavenging affinity towards critical radicals (hydroxyl and peroxyl). It induced lymphocyte growth and modulated the macrophage functions into an anti-inflammatory profile, via elevating macrophage proliferation and its binding affinity of fluorescein isothiocyanate-lipopolysaccharide (FITC-LPS) and inhibiting nitric oxide and tumor necrosis factor-α generation. Furthermore, SCE showed a potent cytotoxicity against human breast MCF-7 carcinoma cells (IC 50 27.73 µg/mL), whereas SCE treatment inhibited the activity of histone deacetylase (HDAC IC 50 37.70 µg/mL) and disturbed the pattern of cell cycle phases. An arrest in both S- and G2/M-phases was linked with shifted cell populations towards late apoptosis and necrosis, as detected by flow cytometry. SCE is a promising cancer chemopreventive agent to be used in healthy food industries and for the high breast cancer-risk population.